Ginsenoside Rg3 alleviates septic liver injury by regulating the lncRNA TUG1/miR-200c-3p/SIRT1 axis - Pan Wu; Xiao Yu; Yue Peng; Qian-Lu Wang; Long-Tian Deng; Wei Xing (BMC, 2021)
Abstract Background Studies have shown that ginsenoside R3 (Rg3) plays a protective role in sepsis-induced organ injuries and mitochondrial dysfunction. Long noncoding RNA (lncRNA) taurine-upregulated gene 1 (TUG1) is regarded as a regulator in sepsis. However, the association between TUG1 and Rg3 remains elusive. Methods A sepsis mouse model was established by caecal ligation and puncture (CLP), and liver injury was induced by haematoxylin-eosin (H&E) staining. Lipopolysaccharide (LPS) was used to induce hepatocyte damage. The expression levels of TUG1, microRNA (miR)-200a-3p, and silencing information regulator 1 (SIRT1) were examined by quantitative real-time polymerase chain reaction (qRT-PCR) assays. Cell viability was monitored using the Cell Counting Kit-8 (CCK-8) assay. MitoSOX Red staining and CBIC2 (JC-1) dye were employed to detect mitochondrial reactive oxygen species (ROS) and mitochondrial transmembrane potential (MTP) levels, respectively. The interaction between miR-200a-3p and TUG1 or SIRT1 was confirmed via dual-luciferase reporter or RNA immunoprecipitation (RIP) assay. Results Rg3 upregulated TUG1 expression in liver tissues of CLP mice and LPS-induced hepatocytes. Rg3 could activate autophagy to improve mitochondrial dysfunction in LPS-treated hepatocytes, which was partially reversed by TUG1 depletion or miR-200a-3p overexpression. Importantly, TUG1 targeted miR-200a-3p to activate the SIRT1/AMP-activated protein kinase (AMPK) pathway in LPS-treated hepatocytes. Moreover, gain of TUG1 ameliorated mitochondrial dysfunction in LPS-treated hepatocytes by sequestering miR-200a-3p. Conclusion Our study revealed that Rg3 increased TUG1 expression and reduced miR-200a-3p expression to stimulate the SIRT1/AMPK pathway, thereby enhancing autophagy to improve sepsis-induced liver injury and mitochondrial dysfunction.